The Appropriateness of Family Support in Life Crises: A Determinant of Individual Psychological Well-Being and Vulnerability - Fajar, Abbas Sofwan Matlail; Fauzi, Ahmad (Bulletin of Science, Technology and Society, 2025)
Life crises represent a universal phenomenon that challenges individuals’ adaptive capacities, often resulting in heightened psychological distress. The family serves as a primary source of support; however, the effectiveness of such support is highly contingent upon the congruence between the type of assistance provided and the individual's psychological needs. This review aims to explore how the quality of familial support influences an individual’s ability to manage stress, and how misalignment between the form of support and the nature of the crisis may exacerbate psychological vulnerability. Employing a literature review approach, this study analyzes a range of relevant publications. The findings show that appropriately aligned emotional support can enhance emotional regulation, increase perceived control, and reduce the risk of depression and anxiety. On the other hand, unhelpful support, such as overprotection, excessive instruction, or insufficient validation, may increase psychological burden through mechanisms including emotional alienation, internalization of stigma, disrupted emotional regulation, and the emergence of learned helplessness. Mismatched support also gives rise to intrapersonal and interpersonal conflict, impairs physiological functioning, and decreases long-term resilience. Moreover, familial support demonstrates dual potential, it can serve as either a protective or maladaptive factor, depending on how suitable the support is. This review underscores the critical importance of a comprehensive understanding of the dynamics of family support in the context of life crises. Familial sensitivity to emotional needs and variations in crisis types constitutes a crucial component in safeguarding individual psychological well-being